Combination nivolumab with transcatheter arterial chemoembolization for clinical remission of small cell lung cancer: A case report. Issue 5 (2nd March 2018) - Guo, Ziwei; Meng, Chao; Wei, Xing; Tang, Chuanhao; Liang, Jun
Abstract : The outcome of small cell lung cancer (SCLC) patients is poor because rapid metastasis develops after first‐line chemotherapy and few drugs are available for second‐line chemotherapy. The median survival rate has not significantly changed in recent years. In this report, we discuss the case of a 71‐year‐old Chinese female non‐smoker diagnosed with extensive‐stage SCLC who was treated with nivolumab for a short period and obtained a prolonged clinical benefit. We report the clinical history, clinical features, potential mechanism, benefits, and the best therapeutic window. The patient was treated with transcatheter arterial chemoembolization because of liver metastasis and then with four doses of nivolumab as third‐line systemic treatment. There was no disease progression for 15 months. The lesions became larger than before, suggesting disease progression, thus nivolumab treatment was ceased. Immunotherapy has the capacity to turn combined therapy into a feature that may be exploited for clinical benefit. Further research is required to evaluate whether combined treatment is beneficial for patients, affecting the efficacy of immunotherapy, and to determine the best therapeutic window for clinical treatment.